Advanced reliability modeling II : reliability testing and improvement : proceedings of the 2nd Asian International Workshop (AIWARM 2006), Busan, Korea, 24-26 August 2006 - Dohi, Tadashi; Yun, Won Young (World Scientific, 2006)
The 2006 Asian International Workshop on Advanced Reliability Modeling (AIWARM) is the second symposium in a series of biennial workshops for the dissemination of state-of-art research and the presentation of practice in reliability and maintenance engineering in Asia. It brings together researchers and engineers from not only Asian countries but also all over world to discuss the state of research and practice in dealing with both reliability issues at the system design phase and maintenance issues at the system operation phase. The theme of AIWARM 2006 is "reliability testing and improvement